An analysis of energy use patterns and implications of COb2 (Breduction targets and carbon tax in the urban residential sector of Thailands - Sithisakdi Apichatthanapath; Shrestha, Ram M.; Kumar, Sivanappan; Wang, Y. J.; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
In 2005, the building sector accounted for around 20 per cent of total COb2 (Bemission in Thailand; of which, 70 per cent came from the residential sector. With the population expected to increase, couple with economic growth that comes with a desire to improve one's standard of living, there are reasons to believe that the residential sector' will becoming increasingly recognized as the main source of COb2 (Bemission. Yet, efforts to explore long-term potential of C0b2 (Bmitigating measures in this sector have been limited. This study analyses the implications of three broad categories of emission reduction technical measures: (1) improvement in building insulation, (2) implementation of energy efficient appliances, and (3) installation of low- and zero-carbon technologies. A number of questionnaire samples were conducted in Bangkok to complement available secondary data used, in the development of a physically based bottom-up model, representing the energy demand of Thailand's urban housing stock. Calculation of cooling loads through the use of Carrier's HAP E20-II was made to demonstrate variations of space cooling demand according to different categories of dwellings. MARKAL based energy system model of Thailand has been restructured to integrate these data and was used to assess these measures in terms of COb2 (Breduction potential, energy system cost and energy resource mix during 2005-2050. Three emission reduction target scenarios were made for comparative analysis with the business-as-usual scenario. In addition, the study argues that by giving monetary values/costs to COb2 (Bemission, the carbon reduction benefits may become more evident as well as justified. Such approach was made through implementation of tax scheme on COb2 (Bemissions
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Energy Economics and Planning
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: City dwellers -- Energy consumption -- Thailand; Energy consumption -- Thailand